Fixation and clinical outcome of uncemented peri-apatite-coated versus cemented total knee arthroplasty: five-year follow-up of a randomised controlled trial using radiostereometric analysis (RSA). (November 2017) - van Hamersveld, K. T.; Marang-van de Mheen, P. J.; Tsonaka, R.; Valstar†, E. R.; Toksvig-Larsen, S.
Abstract : Aims: The optimal method of tibial component fixation remains uncertain in total knee arthroplasty (TKA). Hydroxyapatite coatings have been applied to improve bone ingrowth in uncemented designs, but may only coat the directly accessible surface. As peri-apatite (PA) is solution deposited, this may increase the coverage of the implant surface and thereby fixation. We assessed the tibial component fixation of uncemented PA-coated TKAs versus cemented TKAs. Patients and Methods: Patients were randomised to PA-coated or cemented TKAs. In 60 patients (30 in each group), radiostereometric analysis of tibial component migration was evaluated as the primary outcome at baseline, three months post-operatively and at one, two and five years. A linear mixed-effects model was used to analyse the repeated measurements. Results: After five years of follow-up, one (cemented) component was revised due to ligament instability. Overall, uncemented PA-coated tibial components migrated significantly more (p = 0.003), with the mean maximum total point motion (MTPM) at five years being 0.62 mm (95% confidence intervals (CI) 0.49 to 0.76) for cemented tibial components and 0.97 mm (95% CI 0.81 to 1.15) for PA-coated tibial components in TKA. However, between three months and five years the cemented TKAs migrated significantly more (p = 0.02), displaying a MTPM of 0.27 mm (95% CI, 0.19 to 0.36) versus 0.13 mm (95% CI, 0.01 to 0.25) for PA-coated tibial components. One implant in each group was considered at risk for aseptic loosening due to continuous migration after five years of follow-up, albeit with different migration patterns for each group (i.e. higher initial migration but diminishing over time for the PA-coated component versus gradually increasing migration for the cemented component). Conclusion: The tibial components of PA-coated TKAs showed more overall migration compared with the tibial components of cemented TKAs. However, post hoc analysis showed that this difference was caused by higher migration of PA-coated components in the first three months, after which a stable migration pattern was observed. Clinically, there was no significant difference in outcome between the groups. Cite this article: Bone Joint J 2017;99-B:1467–76.